A high polarity poly(vinylidene fluoride-co-trifluoroethylene) random copolymer with an all-trans conformation for solid-state LiNi0.8Co0.1Mn0.1O2/lithium metal batteries. Issue 35 (16th August 2022) - Zeng, Jian-Ping; Liu, Jun-Feng; Huang, Hua-Dong; Shi, Shao-Cong; Kang, Ben-Hao; Dai, Chen; Zhang, Li-Wei; Yan, Zhi-Chao; Stadler, Florian J.; He, Yan-Bing; Huang, Yan-Fei
Abstract : A unique P(VDF-TrFE) that always shows an all- trans conformation displays a strong polarity to promote the dissociation of lithium salts, increasing the ionic conductivity of solid-state polymer electrolytes to 4.48 × 10 −4 S cm −1 at 25 °C. Abstract : The conventional way to improve the ionic conductivity of solid-state polymer electrolytes (SPEs) is by incorporating inorganic fillers. Although effective, the flexibility of SPEs is sacrificed more or less. Here we propose improving the ionic conductivity of pure SPEs without any help of fillers. This is achieved by enhancing the polarization of polymers through the employment of a unique poly(vinylidene- co -trifluoroethylene) [P(VDF-TrFE)] copolymer as the matrix of SPEs. Compared to common PVDF that tends to show a non-polar trans – gauche (TGTG′) conformation, P(VDF-TrFE) always shows a high polarity all- trans (TTTT) conformation when the TrFE content ranges from 20 to 50 mol%. Results show that P(VDF-TrFE) 80/20 mol% employed in this study has a much higher remnant polarization (79.1 mC m −2 ) than PVDF (12.8 mC m −2 ). In consequence, the dissociation of LiN(SO2 CF3 )2 is facilitated, which endows P(VDF-TrFE) SPEs with remarkably enhanced ionic conductivity (4.48 × 10 −4 S cm −1 ) at 25 °C compared to pure PVDF SPEs reported in the literature (≤10 −5 S cm −1 ). The LiNi0.8 Co0.1 Mn0.1 O2 (NCM811)/P(VDF-TrFE) SPEs/Li batteries present stable cycling at 1C and 2C at 25 °C while the controlled NCM811/PVDF SPEs/Li batteries exhibit a dramatic capacity decay. The Li/P(VDF-TrFE) SPEs/Li batteries stably cycle for nearly 2000 h without a short circuit. This work provides a new strategy and paves the way for a new research area for novel SPEs by regulating the polarity of host polymers.